Highly porous reduced graphene oxide-coated carbonized cotton fibers as supercapacitor electrodes - Baena-Moncada, Angélica María (2020)
High-surface-area carbon-based capacitors exhibit significant advantages relative to conventional graphite-based systems, such as high power density, low weight, and mechanical flexibility. In this work, novel porous carbon-based electrodes were obtained from commercial cotton fibers (CFs) impregnated with graphene oxide (GO) at different dipping times. A subsequent thermal treatment under inert atmosphere conditions enables the synthesis of electrodes based on reduced GO (RGO) supported on carbon fibers. Those synthetized with 15 min and 30 min of dipping time displayed high specific capacitance given their optimal micro-/ mesoporosity ratio. Particularly, the RGO/CCF15A supercapacitor reports a remarkable specific capacitance of 74.1 F g−1 at 0.2 A g−1 and a high cycling stability with a 97.7% capacitive retention, making this electrode a promising candidate for supercapacitor design. Finally, we conducted a density functional theory study to obtain deeper information about the driving forces leading to the GO/CF structures.